2009
DOI: 10.1109/tasc.2009.2017950
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nb/Al-AlN/NbTiN SIS Junctions With ICP Nitridation

Abstract: Increasing the operating frequency of SIS receivers requires a shift from Nb Al AlO X Nb junctions to new material systems. Two major limiting factors of higher frequency operation are the increase in subgap leakage that occurs in AlO X barriers as current densities approach and exceed 10 kA cm 2 and the increased loss in Nb electrodes above 700 GHz. A promising alternative structure is the hybrid Nb/Al-AlN/NbTiN junction. Realization of these devices has been difficult due to the challenge of fabricating devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[34] to nitridation of Al films via parallel-plate plasma [35], ion gun [36], and ICP [24]. Previous attempts at trilayer growth utilizing ICP grown AlN barriers at UVML produced fairly low-leakage high-quality SIS junctions, however it was shown that the repeatability of the normal state resistance junction area product, ( ), of successive wafers drifted over time by up to an order of magnitude [38]. The ability to predict and control junction impedance is paramount to the realization of superconducting RF circuits, such a drift in is a limiting factor.…”
Section: Reduction In Junction Area Raises Its Own Difficulties In Rementioning
confidence: 99%
See 1 more Smart Citation
“…[34] to nitridation of Al films via parallel-plate plasma [35], ion gun [36], and ICP [24]. Previous attempts at trilayer growth utilizing ICP grown AlN barriers at UVML produced fairly low-leakage high-quality SIS junctions, however it was shown that the repeatability of the normal state resistance junction area product, ( ), of successive wafers drifted over time by up to an order of magnitude [38]. The ability to predict and control junction impedance is paramount to the realization of superconducting RF circuits, such a drift in is a limiting factor.…”
Section: Reduction In Junction Area Raises Its Own Difficulties In Rementioning
confidence: 99%
“…Upon the start of my PhD research, our research group had demonstrated the ability to produce fairly low-leakage high-quality Nb/Al-AlN/Nb SIS junctions utilizing ICP grown AlN barriers, however, it was shown that the repeatability of , drifted over time by up to an order of magnitude [38]. Such a drift in made it impossible to realize SIS based mixers of proper design impedance.…”
Section: Modifications To Trilayer Deposition Systemmentioning
confidence: 99%
“…Moreover, ultrathin superconducting films are known to exhibit extremely high values of the critical magnetic field H c . 8 The ability to maintain (or even increase) the T c of a superconducting coating while keeping its critical magnetic field at the same level as for the ultrathin films can lead to many advances in technological applications of superconductors such as THz SIS (superconductor/insulator/superconductor) receivers, 9,10 superconducting single photon detectors (SNSPDs), 11 qubits, and quantum electronics. [12][13][14] Multilayered SIS metamaterial coatings with tailored thicknesses for superconductor and insulator materials are foreseen to shield vortex penetration and enhance the maximum sustainable magnetic field for niobium cavities used in particle accelerators.…”
Section: Introductionmentioning
confidence: 99%